Imagery and Agility Training: How do They Affect the Reaction Ability of Futsal Goalkeepers? - Rozi, Muhammad Fakhrur; Resmana, Riand; Selviani, Iit; Okilanda, Ardo; Sumantri, Riyan Jaya; Suganda, Mikkey Anggara; Suryadi, Didi (Physical Education Theory and Methodology, 2023)
Study purpose. Goalkeepers in futsal require fast movements to anticipate the ball that is heading toward the goal. Therefore, the reaction of the goalkeeper is very necessary to improve the quality in the game. Materials and methods. This research is experimental research conducted using factorial design research using a quantitative approach. In this research, the researchers use treatment with imagery exercises, with audiovisual and visual methods, with measuring the level of ability and agility of each sample in a group experiment. The type of instrument used to measure the ability of the goalkeeper’s reaction speed in this study is the whole-body reaction test. The population in this study was high school (SMA) students who played futsal goalkeepers throughout the city of Metro, with the number of participants being 90 students of 9 high schools throughout the city of Metro. Purposive sampling technique was used so that a sample of 24 students was obtained. Results. The results of the study prove that the significance value of imagery training is 0.001 < 0.05 which means "Ha is accepted", then there is an effect of Imagery training on the goalkeeper's reaction time. Next, the significance value of Agility training is 0.018 <0.05, which means "Ha is accepted", then there is an effect of agility training on the goalkeeper's reaction time. There is a significant difference between imagery training using audiovisual, high agility, and imagery training using audiovisual, low agility, with a significance value of 0.016. While there is no significant difference between imagery exercises using visuals, high agility and imagery exercises using visuals, low agility with a significance value of 0.395. Conclusions. Based on the results, it can be concluded that imagery and agility exercises have a significant effect on the reaction time of goalkeepers in futsal.